2019
DOI: 10.1093/cz/zoz026
|View full text |Cite
|
Sign up to set email alerts
|

Bumblebees adjust protein and lipid collection rules to the presence of brood

Abstract: Animals have evolved foraging strategies to acquire blends of nutrients that maximize fitness traits. In social insects, nutrient regulation is complicated by the fact that few individuals, the foragers, must address the divergent nutritional needs of all colony members simultaneously, including other workers, the reproductives, and the brood. Here we used 3D nutritional geometry design to examine how bumblebee workers regulate their collection of 3 major macronutrients in the presence and absence of brood. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 68 publications
(96 reference statements)
2
47
0
Order By: Relevance
“…Recent studies have demonstrated further associations between bee foraging preferences and health and pollen P:L ratios. For example, entire bumble bee colonies regulate protein and lipids to similar ratios as we predicted previously [10]. We found that the P:L of different pollens used in agricultural cover-cropping systems have differential effects on B. impatiens colony ovary activation and wax production [20]; we also found that P:L ratios and the protein content of an invasive plant species may be more attractive to the bee community (including solitary bees) than surrounding native plants, presenting a possible mechanism of invasive competitive ecology [19].…”
Section: Introductionsupporting
confidence: 73%
See 3 more Smart Citations
“…Recent studies have demonstrated further associations between bee foraging preferences and health and pollen P:L ratios. For example, entire bumble bee colonies regulate protein and lipids to similar ratios as we predicted previously [10]. We found that the P:L of different pollens used in agricultural cover-cropping systems have differential effects on B. impatiens colony ovary activation and wax production [20]; we also found that P:L ratios and the protein content of an invasive plant species may be more attractive to the bee community (including solitary bees) than surrounding native plants, presenting a possible mechanism of invasive competitive ecology [19].…”
Section: Introductionsupporting
confidence: 73%
“…As data for A. mellifera and O. cornifrons were not collected for systematic analysis, we acknowledge that these trends, while intriguing, require further study with a robust design. It is also likely that bee species' preferences and nutritional targets may be species, caste, and life-stage specific and not driven simply by higher or increasing nutrient concentrations or ratios [6,10,56]. Furthermore, bee foraging for particular pollen nutritional values may be attenuated by the limits of landscape availability.…”
Section: P:l Trends In Bee-flower Interactionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, the bees' movements shifted to include the land use categories with greater pollen heterogeneity [75,76] despite continued, albeit reduced, availability of blueberry flowers. Results from Kraus et al (2019) [77], who studied Bombus diets in captivity, also suggest that protein levels are critical for larval development, and these protein levels may be sustained from the more diverse plants.…”
Section: Plos Onementioning
confidence: 98%